2014
DOI: 10.1038/ng.3090
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies three susceptibility loci for laryngeal squamous cell carcinoma in the Chinese population

Abstract: To identify genetic markers for laryngeal squamous cell carcinoma (LSCC), we conducted a genome-wide association study (GWAS) on 993 individuals with LSCC (cases) and 1,995 cancer-free controls from Chinese populations. The most promising variants (association P < 1 × 10(-5)) were then replicated in 3 independent sets including 2,398 cases and 2,804 controls, among which we identified 3 new susceptibility loci at 11q12 (rs174549), 6p21 (rs2857595) and 12q24 (rs10492336). The minor alleles of each of these loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 34 publications
4
64
1
Order By: Relevance
“…To date, only a GWAS study revealed that FADS1 polymorphism (rs174549) showed a protective effect on LSCC [8]. This finding is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To date, only a GWAS study revealed that FADS1 polymorphism (rs174549) showed a protective effect on LSCC [8]. This finding is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the present results. Although the mechanism of rs174549 polymorphism on oral cancer is not clear, previous study found there were 49 SNPs in high linkage disequilibrium with rs174549 in the same chromosome, and these SNPs might influence the expression of FADS1 through their effects on host genes [8]. Moreover, FADS1 variation could suppress inflammatory response through influencing the metabolism of PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 SNPs analyzed here were identified in LC genome-wide association studies [8–10]. All of the SNPs had minor allele frequencies of > 5% in the HapMap for the Chinese Han Beijing population.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several separate genome-wide association scans have demonstrated that common SNPs, including those in the leucine rich repeat and fibronectin type III domain containing 2 ( LRFN2 ), cyclin-dependent kinase inhibitor 1A ( CDKN1A ), brain-specific angiogenesis inhibitor 3 ( BAI3 ), and parkin RBR E3 ubiquitin protein ligase ( PARK2 ) genes, are associated with LC prognosis. All of these genes are located on Chromosome 5, 6, or 7 [8–10]. …”
Section: Introductionmentioning
confidence: 99%